Different Tissue Plasminogen Activator Release in the Arm and Leg during Venous Occlusion Is Equalized after DDAVP Infusion - Keber, Dušan; Stegnar, Mojca; Kluft, Cornelis (Thrombosis and Haemostasis, 1990)
The mechanism of tissue plasminogen activator (t-PA) release during arm and leg venous occlusions and DDAVP (1 desamino- 8-D-arginine vasopressin) infusion was studied in 10 healthy males. The following determinations were carried out on venous blood: t-PA antigen (ELISA), t-PA activity, and t-PA inhibitor (PAI) activity (amidolytic assays). Before DDAVP, there was a 270% t-PA antigen increase in the arm at the end of occlusion as opposed to only a 40% increase in the leg. After DDAVP, t-PA antigen at the end of arm and leg occlusion reached an equal level which was significantly higher than in the arm before DDAVP. The study produced no evidence of PAI release during venous occlusion of a limb. It is concluded that DDAVP is able to elicit t-PA release from arm as well as from leg vessels. The poor fibrinolytic response of leg vessels to venous occlusion is not due to a high PAT release or t-PA stores depletion in leg vessels, but rather to low basal t-PA release in leg vessels.
Keywords: Tissue plasminogen activator; Venous occlusion; DDAVP; Mechanism of release